Measurement of electrons from beauty-hadron decays in p-Pb collisions at √sNN=5.02 TeV and Pb-Pb collisions at √sNN=2.76 TeV - Adam, Jaroslav; Angelov, Venelin; Arslandok, Mesut; Beck, Hans; Danisch, Meike; Deisting, Alexander; Glässel, Peter; Kim, Jiyoung; Klewin, Sebastian; Knichel, Michael Linus; Leardini, Lucia; Mercado Pérez, Jorge; et al. (Journal of high energy physics, 2017)
The production of beauty hadrons was measured via semi-leptonic decays at mid-rapidity with the ALICE detector at the LHC in the transverse momentum interval 1<p T < 8 GeV/c in minimum-bias p-Pb collisions at sNN−−−√=5.02sNN=5.02 \sqrt{s_{NN}}=5.02 TeV and in 1.3 < p T < 8 GeV/c in the 20% most central Pb-Pb collisions at sNN−−−√=2.76sNN=2.76 \sqrt{s_{NN}}=2.76 TeV. The pp reference spectra at sNN−−−√=5.02sNN=5.02 \sqrt{s_{NN}}=5.02 TeV and s√=2.76s=2.76 \sqrt{s}=2.76 TeV, needed for the calculation of the nuclear modification factors R pPb and R PbPb, were obtained by a pQCD-driven scaling of the cross section of electrons from beauty-hadron decays measured at s√=7s=7 \sqrt{s}=7 TeV. In the p T interval 3 < p T < 8 GeV/c, a suppression of the yield of electrons from beauty-hadron decays is observed in Pb-Pb compared to pp collisions. Towards lower p T, the R PbPb values increase with large systematic uncertainties. The R pPb is consistent with unity within systematic uncertainties and is well described by theoretical calculations that include cold nuclear matter effects in p-Pb collisions. The measured R pPb and these calculations indicate that cold nuclear matter effects are small at high transverse momentum also in Pb-Pb collisions. Therefore, the observed reduction of R PbPb below unity at high p T may be ascribed to an effect of the hot and dense medium formed in Pb-Pb collisions. Open image in new window
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
ALICE Collaboration: J. Adam, V. Anguelov, M. Arslandok, H. Beck, M.C. Danisch, A. Deisting, P. Glässel, J. Kim, S. Klewin, L. Leardini, J. Mercado Pérez, A. Ohlson, Y. Pachmayer, K. Reygers, R. Schicker, J. Stachel, D.F. Weiser, B. Windelband [und weitere]
Gesehen am 18.08.2020